Peran Guru dalam Mengembangkan Kreativitas Kelas V Melalui Kegiatan Seni di SD - Yeni Nuraeni; Siti Sholikha; Nadya Prima Wulandari; Mutiara Erlita Romli; Wurinda Nur Baiti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This research aims to analyze the role of teachers in developing the creativity of fifth grade students through art activities in elementary schools. Teachers act as educators, tutors, mentors, motivators and evaluators who create creative and innovative learning. Fine arts education is oriented towards developing creative thinking abilities, creative skills and art appreciation. Supporting factors in the form of infrastructure, school culture, the role of teachers, and extracurricular activities can increase student creativity. However, there are obstacles such as limited facilities, teacher competence, family support, and curriculum time. Solutions include collaboration with the arts community, teacher training, parent education, and integration of the arts in other subjects.